Drug Resistance in Parasitic Diseases - Ertabaklar, Hatice; Malatyalı, Erdoğan; Ertuğ, Sema (European Journal of Therapeutics, 2023)
Owing to the lack of or the ineffectiveness of vaccines for life-threatening parasitic diseases, chemotherapy is the current strategy to prevent parasitic diseases. Drug resistance disrupts chemotherapeutic options, thereby increasing the need for novel drugs in parasitological treatments. The most common resistance mechanisms are decreased drug uptake, export of drugs from parasites, genetic modifications, loss of drug activity, and alteration of the drug target. Drug resistance mechanisms should be well defined to develop new strategies to control parasitic diseases. This measure will ensure new effective treatment options for clinicians. In the recent years, isolation and characterization of resistance-related genes and proteins has considerably increased our knowledge. This review mostly focuses on new studies and common parasitic diseases.